Welfare reform in rural places comparative perspectives - Milbourne, Paul, 1966-; Marsden, Terry (Bingley, U.K. : Emerald, 2010)
Research on welfare has tended to focus on the national scale with relatively little attention given to the differential impacts of welfare restructuring in rural places and the difficulties faced by disadvantaged groups with limited provision of welfare services in many rural areas. This book seeks to significantly extend previous research work on the rural impacts of national welfare reform and position it in a broader context. "International Perspectives on Rural Welfare" provides a critical, comprehensive and comparative account of the rural dimensions of welfare in a number of developed countries. The book brings together recent research from Europe, North America, Australia and New Zealand to provide the seminal international book on rural welfare. As well as being international in its outlook, it provides an inter-disciplinary focus on rural welfare by including contributors from sociology, human geography, social policy and social anthropology. The definition of welfare used within the book is broad, encompassing overarching welfare and workfare agendas, as well as more specific welfare policy areas such as anti-poverty, health, housing, social security, social work and education.
ch. 1. Scaling and spacing welfare reform : making sense of welfare in rural places / Paul Milbourne -- ch. 2. Impacts of welfare reform on rural people and places in the United States / Bruce Weber, Mindy Crandall -- ch. 3. Devolution, social exclusion, and spatial inequality in U.S. welfare provision / Ann R. Tickamyer, Debra A. Henderson -- ch. 4. Color-blind welfare reform or new cultural racism? : evidence from rural Mexican- and Native-American communities / Mark H. Harvey, Kathleen A. Pickering -- ch. 5. Social welfare policies and rural Canada / Bill Reimer -- ch. 6. Placing welfare in rural England / Paul Milbourne -- ch. 7. Rural welfare to work in Wales : young people's experiences / Suzie Watkin -- ch. 8. Giving up farming and the welfare state restructuration in Finland / Sakari Hänninen, Tiina Silvasti -- ch. 9. Shifting welfare, shifting people : rural development, housing and population mobility in Australia / Rae Dufty, Chris Gibson -- ch. 10. Australia's rural welfare policy : overlooked and demoralised / Margaret Alston -- ch. 11. School closures as breaches in the fabric of rural welfare : community perspectives from New Zealand / Robin A. Kearns ... [et al.].
Print version record
Keywords: Social Science -- Human Services; Political Science -- Public Policy -- Regional Planning; Social Science -- Sociology -- General; Social welfare & social services; Rural planning; Public welfare; Rural poor; Rural conditions